ANALISA FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS X KABUPATEN MALANG - Neni Probosiwi; Lintang Bismantara; Elly Megasari; Nur Fahma Laili; Tsamrotul Ilmi; Arifani Siswidiasari (Jurnal Buana Farma, 2024)
Abstract Arterial blood pressure higher than 140/90 mmHg when measured in a calm state is known as hypertension. This study aims to evaluate the factors associated with the incidence of hypertension in Health Center X Malang Regency. This study used an experimental observational design with a cross-sectional approach. The number of respondents included in this study was 74 respondents. The number of samples taken was 74 respondents. Male respondents were 20 respondents (27.02%), female respondents were 54 respondents (72.98%). Respondents who experienced prehypertension were 13 respondents (17.56%), Stage I hypertension was 30 respondents (40.54%), Stage II hypertension was 31 respondents (41.90%). Independent variables include: gender, family history, physical activity, smoking habits, diet, rest needs. The dependent variable is: Hypertension. Analysis results using the square test with α = 0.05 (p < α) obtained results: gender (p = 0.009), family history (p = 0.021), physical activity (p = 0.047), smoking habits (p = 0.002), diet (p = 0.032), rest needs (p = 0.002) have a relationship with the incidence of hypertension in the elderly at Health Center X Malang Regency.